Incidence and Risk Factors of Postoperative Bleeding in Patients Undergoing Total Thyroidectomy - Sun, Ning; Zhang, Danhua; Zheng, Shouhua; Fu, Lijun; Li, Liwen; Liu, Senyuan; Li, Hongting; Qiu, Xinguang (Frontiers in Oncology, 2020)
Purpose: Our goal was to analyze postoperative bleeding in patients undergoing total thyroidectomy and to explore the possible risk factors. Materials and Methods: Patients undergoing total thyroidectomy were retrospectively enrolled, and the main study outcomes were postoperative bleeding and 30-day mortality. Univariate and multivariate analyses were used to determine the independent risk factors for postoperative bleeding. Results: A total of 31706 patients were enrolled for analysis during January 2010 and December 2018 from the Affiliated First Hospital of Zhengzhou University. Benign and malignant disease was reported in 4521 and 27185 patients, respectively. Postoperative bleeding occurred in 48 patients with benign disease and in 263 patients with malignant disease. There was one bleeding site in 243 patients. The branch of the superior thyroid artery was the most common arterial bleeding site, occurring in 124 patients, and the anterior jugular vein was the most common venous bleeding site, occurring in 85 patients. Multivariable analysis confirmed that hypertension, diabetes, BMI, and disease pathology were independent factors affecting postoperative bleeding in patients with benign disease and that hypertension, diabetes, BMI, operation time, tumor stage, and tracheotomy were independent factors affecting postoperative bleeding in patients with malignant disease. In patients with postoperative bleeding, there were 5 deaths; in patients without postoperative bleeding, there were 42 deaths, and the difference was significant (p<0.001). Conclusions: Compared with malignant disease patients, benign disease patients have a similar postoperative bleeding rate; A previous history of chemotherapy or radiotherapy has no significant effect on postoperative bleeding.